Forest biomes of Southern Africa - Ladislav Mucina; Mervyn C. Lötter; Michael C. Rutherford; Adriaan van Niekerk; Paul D. Macintyre; James L. Tsakalos; Jonathan Timberlake; Janine B. Adams; Taryn Riddin; Lauren K. Mccarthy (New Zealand Journal of Botany, 2022)
The forests of South Africa and the neighbouring countries, including Lesotho, eSwatini, Namibia, Botswana, Zimbabwe, and Mozambique (south of the Zambezi River), were mapped and classified according to the global system of biomes. The new four‐tier hierarchical biome system suggested in this paper includes zonobiome, global biome, continental biome (all recognised earlier), and regional biome – a novel biome category. The existing spatial coverages of the forests were revised and considerably improved, both in terms of forest‐patch coverage and mapping precision. Southern Africa is home to three zonal forest types, namely Subtropical Forests (Zonobiome I), Tropical Dry Forest (TDF; Zonobiome II) and Afrotemperate Forests (Zonobiome X). These three biomes are characterised by unique bioclimatic envelopes. Five, two, and eight regional biomes, respectively, have been recognised within these zonal biomes. Recognition of the Zonobiome I and the global biome Tropical Dry Forests in southern Africa is novel and expands our knowledge of the biome structure of African biotic communities. The system of the azonal regional biomes is also new and comprehensively covers the variability of the azonal helobiomes (riparian woodlands and swamp forests), mangroves, and azonal coastal forests. In total, 11 azonal regional biomes have been recognised in the study area. The forest biomes in southern Africa were captured in our electronic map in the form of more than 60 000 polygons, covering 42 416 km 2 (1.27% of the study area). No less than 83% of these forests occur in the territory of southern Mozambique.

Two new species from the mountains of southern Malawi and northern Mozambique - Iain Darbyshire; Roger M. Polhill; Zacharia Magombo; Jonathan R. Timberlake (Kew Bulletin, 2021)
Summary Two new species are described from the proposed Mulanje-Namuli-Ribáuè Centre of Endemism. Isoglossa perdita I.Darbysh. (Acanthaceae) is apparently restricted to the submontane forests of southeastern Mt Mulanje in Malawi, and is assessed as Critically Endangered. Agelanthus patelii Polhill & Timberlake (Loranthaceae) is recorded from the montane forests of Mt Mulanje and from Mt Namuli in Mozambique, and the earlier assessment of this species as Endangered is confirmed. The habitat preferences and taxonomic affinities of these species are discussed. This work contributes to the ongoing assessment of the biodiversity and endemism of this montane region, and to the identification of Important Plant Areas in Mozambique.

The global abundance of tree palms - Robert Muscarella; Thaise Emilio; Oliver L. Phillips; Simon L. Lewis; Ferry Slik; William J. Baker; Thomas L. P. Couvreur; Wolf L. Eiserhardt; Jens‐Christian Svenning; Kofi Affum‐Baffoe; Shin‐Ichiro Aiba; Everton C. de Almeida; et al. (Global Ecology and Biogeography, 2020)
Aim Palms are an iconic, diverse and often abundant component of tropical ecosystems that provide many ecosystem services. Being monocots, tree palms are evolutionarily, morphologically and physiologically distinct from other trees, and these differences have important consequences for ecosystem services (e.g., carbon sequestration and storage) and in terms of responses to climate change. We quantified global patterns of tree palm relative abundance to help improve understanding of tropical forests and reduce uncertainty about these ecosystems under climate change. Location Tropical and subtropical moist forests. Time period Current. Major taxa studied Palms (Arecaceae). Methods We assembled a pantropical dataset of 2,548 forest plots (covering 1,191 ha) and quantified tree palm (i.e., ≥10 cm diameter at breast height) abundance relative to co‐occurring non‐palm trees. We compared the relative abundance of tree palms across biogeographical realms and tested for associations with palaeoclimate stability, current climate, edaphic conditions and metrics of forest structure. Results On average, the relative abundance of tree palms was more than five times larger between Neotropical locations and other biogeographical realms. Tree palms were absent in most locations outside the Neotropics but present in >80% of Neotropical locations. The relative abundance of tree palms was more strongly associated with local conditions (e.g., higher mean annual precipitation, lower soil fertility, shallower water table and lower plot mean wood density) than metrics of long‐term climate stability. Life‐form diversity also influenced the patterns; palm assemblages outside the Neotropics comprise many non‐tree (e.g., climbing) palms. Finally, we show that tree palms can influence estimates of above‐ground biomass, but the magnitude and direction of the effect require additional work. Conclusions Tree palms are not only quintessentially tropical, but they are also overwhelmingly Neotropical. Future work to understand the contributions of tree palms to biomass estimates and carbon cycling will be particularly crucial in Neotropical forests.

Robert Drummond 1924 – 2008 - Jonathan Timberlake; Tom Muller; Mark Hyde; Meg Coates Palgrave (Kew Bulletin, 2008)

Letter - Paul P. Smith; Porter P. Lowry; Jonathan Timberlake; Janice S. Golding (Conservation Biology, 2004)

How Taxonomists Can Bridge the Gap Between Taxonomy and Conservation Science - Janice S. Golding; Jonathan Timberlake (Conservation Biology, 2003)